Corn Injury from Foliar Zinc Application Does Not Affect Grain Yield. (1st September 2016) - Golden, Bobby R.; Orlowski, John M.; Bond, Jason A.
Abstract : Zinc deficiency symptoms have been observed on corn ( Zea mays L.) grown on coarse‐textured, high‐pH soils in the Mississippi Delta. To correct deficiencies, many corn producers apply foliar Zn. Corn injury from foliar Zn application has been observed; however, it is not clear whether foliar Zn injury affects grain yield. Also, little information currently exists about the ability of foliar Zn sources to increase corn tissue Zn concentration. Therefore, the purpose of this study was to determine the effect of Zn source and Zn application rate on foliar injury, tissue Zn concentration, and grain yield in corn. Zinc‐citrate, Zn–ethylenediaminetetraacetic acid (EDTA), and ZnSO4 were applied to corn at 0.56, 1.12, and 2.24 kg Zn ha −1 at V4. Corn injury was evaluated 3, 6, and 9 d after application, and tissue Zn concentration was determined 2 wk after Zn application. Grain yield was determined at harvest. Zinc‐citrate imparted the greatest injury at all application rates, followed by ZnSO4 and Zn‐EDTA. Injury generally increased as Zn application rate increased. The 0.56 kg Zn ha −1 rate resulted in similar tissue Zn content across all Zn sources. Zinc‐citrate and ZnSO4 application resulted greater tissue Zn content than Zn‐EDTA at 1.12 and 2.24 kg Zn ha −1 rates. Despite high levels of foliar injury observed for some Zn sources and rates, no differences in grain yield were observed. Citrate‐Zn application to corn caused more foliar injury than EDTA‐Zn and Zinc sulfate. Citrate‐Zn resulted in highest corn tissue Zn concentrations. Corn injury from foliar Zn application did not affect grain yield.